PEMANFAATAN SERBUK KULIT MANGGIS (Garcinia Mangostana) UNTUK PENYERAPAN ION SENG (II) - Elda Gusneri; Bayharti Bayharti; Erda Sofjeni (Jurnal Periodic Jurusan Kimia UNP, 2013)
One of types enviromental population are water that makey it by heavy metals to enter the water. To put the heavy metals can do with used material that absorb, that cheap we chan anywhere. One of the material is Garcinia Mangostana. This resert determination to known optimum condition absorbet from zing (II) ions by Garcinia mangostana, with variety particles size : 75, 90 and 109µm, pH : 3, 4, 5, 6, 7 dan 8, and concentration zing (II) ions solution : 10, 20, 30, 40 and 50 ppm. The measurment used by Atomic Absorption Spektrophotometer. From this yield resert found absorbant optimum condition zing (II) ions by Garcinia Mangostana can happened in particles size 75µm, pH 5 and concentration zing (II) ions solution 30 ppm with absorbent capacity 0,4250 mg/g.